2017
DOI: 10.1017/wet.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Postemergence Weed Control in Onion with Bentazon, Flumioxazin, and Oxyfluorfen

Abstract: Field experiments were conducted in 2008 and 2010 to determine crop tolerance and weed control efficacy of the POST herbicides bentazon, flumioxazin, and oxyfluorfen applied to direct-seeded dry bulb onions on organic soil. Postemergence application of oxyfluorfen at 0.071 kg ai ha−1resulted in less than 20% onion injury when applied at the 2 and 4 onion leaf stages and provided good control of ladysthumb and common lambsquarters. Oxyfluorfen EC caused slightly higher visual injury than oxyfluorfen SC, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
1
6
0
1
Order By: Relevance
“…This inhibition of photosynthesis and oxidative stress is followed by cell damage (Dat et al, 1998;Han and Wang, 2002). In agreement with previous reports (Diebold et al, 2004;Herrmann et al, 2017;Lima et al, 2018), our results indicated the bentazon could interfere with Under stress conditions, plants usually generate higher levels of ROS, which subsequently induce peroxidation of membrane lipids and oxidative damage (Kar, 2011;Munn e-Bosch and Peñuelas, 2003). Melatonin is a plant growth regulator that improves photosynthetic efficiency in higher plants under stressful conditions (Jiang et al, 2016;Yin et al, 2013;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This inhibition of photosynthesis and oxidative stress is followed by cell damage (Dat et al, 1998;Han and Wang, 2002). In agreement with previous reports (Diebold et al, 2004;Herrmann et al, 2017;Lima et al, 2018), our results indicated the bentazon could interfere with Under stress conditions, plants usually generate higher levels of ROS, which subsequently induce peroxidation of membrane lipids and oxidative damage (Kar, 2011;Munn e-Bosch and Peñuelas, 2003). Melatonin is a plant growth regulator that improves photosynthetic efficiency in higher plants under stressful conditions (Jiang et al, 2016;Yin et al, 2013;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…However, the improper use of some pesticides in the onion crop may still cause health risks from onion consumption. Several studies have been carried out to investigate the degradation behavior, residue distribution, and dietary risk of different pesticides, including insecticides (17, 192), fungicides (193)(194)(195), and herbicides (196), which were used for pest and disease protection and weed control in onion planting. Overall, the dietary risk of these pesticides through onion could be negligible with the reasonable usage does of pesticides and enough preharvest interval (Table 2).…”
Section: Pesticide Residuementioning
confidence: 99%
“…where the most common weed was nettleleaf goosefoot (Chenopodium murale) (Qasem, 2007). Broadleaf weed control outcomes for pendimethalin, S-metolachlor, and dimethenamid-P can be improved with additional herbicides in the spray solution (Grichar, 2007;Hutchinson, 2012); however, some tank mixtures may increase risk of onion injury compared with herbicides applied alone (Herrmann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible strategy for increasing seaside petunia susceptibility to foliar applications of oxyfluorfen is to apply an emulsifiable concentrate (EC) formulation of oxyfluorfen rather than the water-based suspension concentrate (SC) formulation used in our study, because a previous study determined that an EC formulation of oxyfluorfen improved control of specific broadleaf weeds when compared against a SC formulation (Herrmann et al, 2017). The EC formulation also caused more foliar injury on onions, but there was no difference in onion bulb yield between the EC and SC formulations of oxyfluorfen (Herrmann et al, 2017).…”
Section: Discussionmentioning
confidence: 99%